Descriptive Analysis of Typhoid Fever Surveillance Data in the Jimma Zone, Southwest Ethiopia (2015–2019) - Atikilt Yemata, Getaneh; Yenew, Chalachew; Mamuye, Melkalem; Tiruneh, Mulu; Assfaw, Tigabnesh; Mulatu, Sileshi; Sisay, Ermias; Tadele, Fitalew (Interdisciplinary Perspectives on Infectious Diseases, 2021)
Introduction. Typhoid fever is a major cause of morbidity and mortality around the globe, and it is a serious illness in developing countries. Typhoid fever is prevalent in Ethiopia, and the burden differs with diverse demography, environment, and climate. The study aimed to determine the incidence of typhoid fever cases by person, place, and time. Method. A descriptive cross-sectional study was conducted among the five years (2015–2019) of surveillance data of typhoid fever in the Jimma Zone, Oromia Region, Ethiopia. The data were extracted from the zonal health management information system database from May to June 2020. SPSS version 21 was used to enter and analyze the data. Descriptive analysis was used to assess the distribution of typhoid fever incidence in time, place, and personal groups. Result. A total of 36,641 individuals suffered from typhoid fever during the five years. Among these, 18,972 (51.8%) were females and 17,669 (48.2%) were males. Incidence of typhoid fever was found as follows: 216, 198, 203, 264, and 299 cases per 100,000 persons were reported during 2015, 2016, 2017, 2018, and 2019, respectively. Typhoid fever cases were increased by 1.4 from 2015–2019. A high incidence of cases was observed at the start of wet months. The majority of the investigated cases were identified in Kersa, 4,476 (12.2%), Gomma, 4,075 (11.1%), and Mana, 3,267 (8.9%), woredas. Of the total, 151 (0.4%) of the reported cases were admitted for inpatient care. During the five years of surveillance data, death was not reported from all woredas. Conclusion and Recommendation. Typhoid fever was a major public health problem in the Jimma Zone for the last 5 years, and it was increased through the years. Zonal health departments should strengthen the interventions focused on the woredas that had a high burden of typhoid fever at the start of the wet months.